MEMBERI SELURUH HIDUP: SEBUAH HERMENEUTIKA ATAS MARKUS 12: 41-44 - Fatima Merlin Rumatora; Gerardus Viany Untu (Pineleng Theological Review, 2026)
This article presents a hermeneutical analysis of Mark 12:41–44 and its parallel in Luke 21:1–4, focusing on the figure of the poor widow within her narrative, socio-historical, and theological contexts. Departing from moralistic interpretations that frame the widow primarily as an exemplar of personal piety or sacrificial generosity, the study argues that the pericope functions as a narrative critique of systemic religious injustice. The methodology combines narrative criticism with historical-social analysis and engages critical perspectives drawn from feminist, social, political, and liberation theology. Particular attention is given to the literary placement of the pericope in Mark’s Gospel and its relationship to Jesus’ critique of scribes and temple-based authority. The analysis demonstrates that the widow operates as a symbolic figure whose offering simultaneously expresses radical trust in God and exposes a religious system sustained by the exploitation of the poor. The article contends that the text does not legitimize self-impoverishment but implicitly challenges structures that normalize such vulnerability. This reading highlights the prophetic dimension of the pericope and its relevance for contemporary ecclesial reflection on faith, justice, and institutional responsibility in contexts of social inequality.